PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN JASA TRANSPORTASI ONLINE GRABBIKE - Hezron Boimau; Juita L D Bessie (Universitas Nusa Cendana, 2021)
This study aims to find out and analyze 1) Perception of customers on the price, quality of service and customer satisfaction of GrabBike online transportation services in Kupang City; 2) impact of Price partially on Customer Satisfaction of GrabBike online transportation service in Kupang City; 3) The partial effect of Service Quality on Customer Satisfaction of GrabBike online transportation services in Kupang City; 4) The effect of Price and Quality of Service simultaneously on the Customer Satisfaction of GrabBike online transportation service customers in Kupang City. The number of samples in this study as many as 100 respondents obtained using accidental sampling techniques. The data was collected using questionnaires, interviews, and literature study. The data analysis techniques used are quantitative descriptive, multiple linear regression analysis and hypothesis testing using SPSS 16 applications. From the results of the analysis showed that: 1) Based on the results of descriptive table analysis respondents gave a very high categorized assessment of the three variables studied; 2) The price partially affects the customer satisfaction of GrabBike Kupang City; 3) the quality of service partially affects the customer satisfaction of GrabBike Kupang City; 4) The price and quality of service simultaneously have a significant impact on the customer satisfaction of GrabBike Kupang City. Based on Adjusted R2 value shows variable contribution of Price and Service Quality to Customer Satisfaction of 57.8%. While 42.2% were influenced by other variables outside the focus of this study. Keywords: Price, Quality of Service and Customer Satisfaction